Associations between biological markers of prenatal stress and infant negative emotionality are specific to sex. (December 2017) - Braithwaite, Elizabeth C.; Murphy, Susannah E.; Ramchandani, Paul G.; Hill, Jonathan
Highlights: Effects of prenatal stress on fetal development may be mediated via glucocorticoids. We report that associations of prenatal cortisol with infant behavior are sex-specific. High maternal prenatal cortisol predicts increased negative emotionality in females. Alternatively, high cortisol predicts reduced negative emotionality in males. The same sex-interaction is evident for maternal salivary alpha-amylase. Abstract: Purpose: Fetal programming is the idea that environmental stimuli can alter the development of the fetus, which may have a long-term effect on the child. We have recently reported that maternal prenatal cortisol predicts infant negative emotionality in a sex-dependent manner: high prenatal cortisol was associated with increased negative emotionality in females, and decreased negative emotionality in males. This study aims to test for this sex-specific effect in a different cohort, and investigate whether sex differences in fetal programming may be specific to glucocorticoid mechanisms by also examining a maternal salivary alpha-amylase (sAA) by sex interaction. Methods: 88 pregnant women (mean gestational age = 27.4 weeks, SD = 7.4) collected saliva samples at home over two working days to be assayed for the hormone cortisol (range = 0.13–88.22 nmol/l) and the enzyme alpha-amylase (range = 4.57–554.8 units/ml). Samples were collected at waking, 30-min post-waking and 12 h post-waking. Two months after birth participants reported infant negative emotionality using the distress to limits subscale of the Infant Behavior Questionnaire. Results: The interaction between maternal prenatal cortisol and infant sex to predict distress to limits approached significance (p = 0.067). In line with our previous finding there was a positive association between prenatal cortisol and negative emotionality in females, and a negative association in males. The interaction between sAA and sex to predict distress was significant (p = 0.025), and the direction of effect was the same as for the cortisol data; high sAA associated with increased negative emotionality in females and reduced negative emotionality in males. Conclusions: In line with our previous findings, this research adds to an emerging body of literature, which suggests that fetal programming mechanisms may be sex-dependent. This is the first study to demonstrate that maternal prenatal sAA may be an important biomarker for infant behavior, and the findings have implications for understanding sex differences in developmental psychopathology.